2001
DOI: 10.1007/pl00012398
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trapidil on ATPase, lipid peroxidation, and correlation with ultrastructure in experimental spinal cord injury

Abstract: The present study was performed to investigate the effect of trapidil on ischemic damage of cells after spinal cord injury. The injury was produced by extradural clip compression of the exposed spinal cord in rats according to Rivlin and Tator. The ten rats in group 1 were used to determine normal findings without any surgery or medication. On the 15 rats in group 2, only six-level laminectomy was performed to determine the influence of the total laminectomy on the biochemical factors measured and the, light a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that trapidil significantly reduces cellular damage and edema in the injury site. This finding is explained by the membrane stabilizing effect of trapidil by inhibition of TXA 2 synthesis [16]. It was reported that trapidil had a marked protection against IR injury in testis.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have shown that trapidil significantly reduces cellular damage and edema in the injury site. This finding is explained by the membrane stabilizing effect of trapidil by inhibition of TXA 2 synthesis [16]. It was reported that trapidil had a marked protection against IR injury in testis.…”
Section: Discussionmentioning
confidence: 92%
“…This finding is explained by the membrane stabilizing effect of trapidil by inhibiting of TXA 2 synthesis. 34 It was reported that trapidil has a marked protection against IR injury in peripheral nerves. 35 It was reported that trapidil has positive effects on anastomotic healing due to its preventive effects on inflammatory response and lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Increased lipid peroxidationcombined with decreased tissue Na + -K + ATPase activity may be associated with an impairment in the interaction of Na + -K + ATPase with membrane phospholipids [27, 28]. In addition, the contribution of oxidative modifications of thiol groups of the enzyme itself may be of importance, as well as the direct inhibitory effect of ethanol reported in vitro [29].…”
Section: Discussionmentioning
confidence: 99%